f(x) = (x + 3)(x + 1)
f(x) = x^2 + x + 3x + 3
f(x) = x^2 + 4x + 3
f'(x) = 2x + 4
-----------------------------------------
Another way to do this
f(x) = (x + 3)(x + 1)
f'(x) = (x + 3)'(x + 1) + (x + 3)(x + 1)'
f'(x) = 1(x + 1) + 1(x + 3)
f'(x) = x + 1 + x + 3
f'(x) = 2x + 4
2007-03-30 09:01:01
·
answer #1
·
answered by Sherman81 6
·
0⤊
0⤋
Two ways to do this
Method 1: product rule:
f'(x) = d(x+3)/dx * (x+1) + d(x+1)/dx * (x+3) = x+1+x+3 = 2x+4
Method two: multiply and use the power rule:
f(x) = x² + 4x + 3
f'(x) = 2x+4
2007-03-30 14:29:03
·
answer #2
·
answered by Pascal 7
·
0⤊
0⤋
For something as simple as this, it's probably best to expand the brackets and differentiate in turn.
So f(x) = x^2 + 4x +3; and f'(x) = 2x+4
2007-03-30 14:28:15
·
answer #3
·
answered by Stephan B 5
·
0⤊
0⤋
f(x) = x² + 4x + 1
f `(x) = 2x + 4
Or could use the Product Rule:-
f `(x) = 1.(x + 1) + 1.(x + 3)
f ` (x) = x + 1 + x + 3
f `(x) = 2x + 4 (as above)
2007-03-30 14:30:17
·
answer #4
·
answered by Como 7
·
0⤊
0⤋
x^2 + 4x + 3
2007-03-30 14:28:25
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
(fg)' = fg' + f' g = (x + 3)' (x + 1) + (x + 3) (x + 1)' = (x +1) + (x + 3) = 2x + 4 = 2(x +2)
2007-03-30 14:31:54
·
answer #6
·
answered by physicist 4
·
0⤊
0⤋
f(x)=x^2+4x+3, the first derivative:
f'(x)= 2x + 4.
2007-03-30 14:28:03
·
answer #7
·
answered by jaime r 4
·
0⤊
0⤋
f(x) = x^2 + 4x + 3
f'(x) = 2x + 4
Easy. Or you can use the product rule.
f'(x) = u'v + v'u
f'(x) = (1)(x + 1) + (1)(x+3)
2007-03-30 14:27:53
·
answer #8
·
answered by tedfischer17 3
·
0⤊
0⤋
f(x)= x^2+4x+3
f`(x) = 2x + 4
2007-03-30 14:30:32
·
answer #9
·
answered by KURTANGLE 4
·
0⤊
0⤋
since its factored its even easier to use (fg)' = f'g + fg'
1*(x+1) + (x+3)*1 = 2x+4
2007-03-30 14:29:45
·
answer #10
·
answered by hustolemyname 6
·
0⤊
0⤋